2024
DOI: 10.1038/s41417-024-00764-w
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneity of hepatocellular carcinoma: from mechanisms to clinical implications

Fatema Safri,
Romario Nguyen,
Shadi Zerehpooshnesfchi
et al.

Abstract: Hepatocellular Carcinoma (HCC) is one of the most common types of primary liver cancer. Current treatment options have limited efficacy against this malignancy, primarily owing to difficulties in early detection and the inherent resistance to existing drugs. Tumor heterogeneity is a pivotal factor contributing significantly to treatment resistance and recurrent manifestations of HCC. Intratumoral heterogeneity is an important aspect of the spectrum of complex tumor heterogeneity and contributes to late diagnos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(2 citation statements)
references
References 96 publications
0
2
0
Order By: Relevance
“…Moreover, the plasticity of CSCs allows them to dedifferentiate back under various stimuli, including those provided by EVs [75]. In addition to the CSC phenotype, because of the tumor heterogeneity, other subpopulations of tumor cells can be detected within the TME [76]. Extracellular vesicles play a significant role in the transfer of an aggressive tumor phenotype to nonaggressive tumor cells, as a result of which the latter acquire the stem cell-like properties [77][78][79].…”
Section: Cancer-derived Evs Transform Cancer Cells Into Cancer Stem C...mentioning
confidence: 99%
“…Moreover, the plasticity of CSCs allows them to dedifferentiate back under various stimuli, including those provided by EVs [75]. In addition to the CSC phenotype, because of the tumor heterogeneity, other subpopulations of tumor cells can be detected within the TME [76]. Extracellular vesicles play a significant role in the transfer of an aggressive tumor phenotype to nonaggressive tumor cells, as a result of which the latter acquire the stem cell-like properties [77][78][79].…”
Section: Cancer-derived Evs Transform Cancer Cells Into Cancer Stem C...mentioning
confidence: 99%
“…showed that by rationally incorporating PI-103, a PI3K/mTOR inhibitor, into liposomes improved systemic injectability and therapeutic effects. 7 Due to these encouraging data, Tang et al. first designed a nanoblocker related to AZD8055, which showed the best antitumor effect among seven tested mTORC1/2 inhibitors.…”
mentioning
confidence: 99%